2019
DOI: 10.1103/physrevb.99.220301
|View full text |Cite
|
Sign up to set email alerts
|

Active Willis metamaterials for ultracompact nonreciprocal linear acoustic devices

Abstract: Willis materials are complex media characterized by four macroscopic material parameters, the conventional mass density and bulk modulus and two additional Willis coupling terms, which have been shown to enable unsurpassed control over the propagation of mechanical waves. However, virtually all previous studies on Willis materials involved passive structures which have been shown to have limitations in terms of achievable Willis coupling terms. In this article, we show experimentally that linear active Willis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…In view of tunability and reconfigurability, active acoustic metamaterials are also attracting increasing attention because the acoustic response can be manipulated through electronically controlled elements and thus can achieve a much wider range of effective parameters [25 . Active acoustic metamaterials have been proved as useful tools to achieve many intriguing physics phenomena, such as PT-symmetric metamaterials [26 , sound isolation meta-atoms [27 , bianisotropic meta-atoms [28 , and topological mechanical metamaterials [29 . Nonetheless, for all types of metamaterials, the tuning depends very much on its actual mechanism in modifying the metamaterial resonance of the physical structures, posing a fundamental challenge to the degree of flexibility and the range of tunability, which is important in many applications requesting real-time tuning.…”
mentioning
confidence: 99%
“…In view of tunability and reconfigurability, active acoustic metamaterials are also attracting increasing attention because the acoustic response can be manipulated through electronically controlled elements and thus can achieve a much wider range of effective parameters [25 . Active acoustic metamaterials have been proved as useful tools to achieve many intriguing physics phenomena, such as PT-symmetric metamaterials [26 , sound isolation meta-atoms [27 , bianisotropic meta-atoms [28 , and topological mechanical metamaterials [29 . Nonetheless, for all types of metamaterials, the tuning depends very much on its actual mechanism in modifying the metamaterial resonance of the physical structures, posing a fundamental challenge to the degree of flexibility and the range of tunability, which is important in many applications requesting real-time tuning.…”
mentioning
confidence: 99%
“…In order to mimic the cochlear wave, it is necessary to study the collective response of these nonlinear subwavelength resonators when they are used as unit cells in the gradient-index metamaterial previously introduced. With this configuration we now enter in the world of active acoustic metamaterials which are known to offer great opportunities to obtain, among other, acoustic diodes [46,47], switches [48] or more complex sound manipulation [49][50][51]. This approach is not in complete agreement with the description of the cochlea since the tonotopy is generally attributed to the gradient in the mechanical properties of the basilar membrane, while only the nonlinearity is attributed to the hair cells [2].…”
mentioning
confidence: 99%
“…We define Δ as the 20 dB IF bandwidth, and calculated it to be 456 Hz for this system, equal to 51% of the peak IF frequency. Other studies utilizing linear mechanisms to achieve nonreciprocity have reported peak IFs of around 40 dB (Δ =4 Hz) for the acoustic circulator [15] and 25 dB (Δ =250 Hz) for the Willis metamaterial [21]. Hence, this proposed mechanism has the potential to exceed the maximum level and bandwidth achieved by other approaches [15], [21] without disrupting mean fluid flow.…”
Section: Resultsmentioning
confidence: 93%
“…Other studies utilizing linear mechanisms to achieve nonreciprocity have reported peak IFs of around 40 dB (Δ =4 Hz) for the acoustic circulator [15] and 25 dB (Δ =250 Hz) for the Willis metamaterial [21]. Hence, this proposed mechanism has the potential to exceed the maximum level and bandwidth achieved by other approaches [15], [21] without disrupting mean fluid flow. Further, the IF spectrum can be easily manipulated by electronically modulating , providing a highly flexible mechanism for in situ optimization of the NSFF system for specific applications.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation